2023
DOI: 10.1039/d3ma00622k
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic carbon and oxygen vacancy engineering on vanadium dioxide nanobelts for efficient aqueous zinc-ion batteries

Xin Gu,
Juntao Wang,
Shuang Wu
et al.

Abstract: This study proposes a synergistic engineering approach involving carbon and oxygen vacancy to improve the performance of VO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…73–75 This excellent supercapacitive behaviour as achieved could mainly be due to the promising morphology of the VO 2 /Mxene. Compared to the recent reports, 76–80 here straightaway vanadium-based nanomaterials (VO 2 nanowires) were employed probably for the first time as a precursor, which is supposed to catalyse the hydrothermal pressure in deforming MXene sheets and helps in the development of a promising nanocomposite with synergistically advanced surface properties. Here, VO 2 nanowires with high surface activity are likely considered to transfer their surface tension to the MXene surface via their confined 1D structures.…”
Section: Resultsmentioning
confidence: 99%
“…73–75 This excellent supercapacitive behaviour as achieved could mainly be due to the promising morphology of the VO 2 /Mxene. Compared to the recent reports, 76–80 here straightaway vanadium-based nanomaterials (VO 2 nanowires) were employed probably for the first time as a precursor, which is supposed to catalyse the hydrothermal pressure in deforming MXene sheets and helps in the development of a promising nanocomposite with synergistically advanced surface properties. Here, VO 2 nanowires with high surface activity are likely considered to transfer their surface tension to the MXene surface via their confined 1D structures.…”
Section: Resultsmentioning
confidence: 99%
“…22 Gu et al reported nitrogen-doped VO 2 (B) nanobelts (VO 2 -N) and carbon-coated VO 2 nanobelts (VO 2 @C), presenting superior electrochemical performances to those of pure VO 2 (B) in AZIBs. 23,24 Liu et al developed K + pre-intercalated V 2 O 5 , carbon-coated V 2 O 5 microspheres, and V 6 O 13 /VO 2 electrode materials, which also exhibit improved electrochemical performance for AZIBs. [25][26][27] Although some achievements have been made, improving the ions diffusion and architecture stability of VO 2 to achieve highperformance AZIBs is still a much-needed study.…”
Section: Introductionmentioning
confidence: 99%